Renin-angiotensin-aldosterone system blockers and region-specific variations in COVID-19 outcomes: findings from a systematic review and meta-analysis - Upinder Kaur; Sankha Shubhra Chakrabarti; Tejas K. Patel (SAGE Publishing, 2021)
Background and aims:  Coronavirus disease 2019 (COVID-19) has been observed to cause a high mortality in people with cardiometabolic diseases. Renin-angiotensin-aldosterone system (RAAS) blockers enhance the expression of ACE2, the binding receptor of SARS-CoV-2, and can enhance viral infectivity. We aim to provide a pooled estimate of the effect of RAAS blockers on COVID-19 outcomes. Methods: A literature search was performed using MEDLINE/PubMed, Google Scholar and preprint servers. All clinical studies analyzing the effect of RAAS blockers on clinical outcomes in COVID-19 patients were included in this study. Newcastle-Ottawa scale was used for quality assessment of studies. MOOSE checklist was followed. Mortality and severity outcomes were recorded as pooled odds ratio (OR) with 95% Confidence Intervals (CIs) and level of heterogeneity ( I 2 ). Odds of mortality was the primary outcome. Odds of severity, hospitalization, intensive care unit (ICU) admission, mechanical ventilation (MV), steroid use and acute kidney injury were the secondary outcomes. Severity outcomes were chosen depending upon the definition used by respective authors. Country-specific variations and effects of individual class of RAAS blockers were also explored. Results: In total 47 published studies were included in the final analysis, with a total of 26,432 patients from 31 studies in mortality analysis and 20,127 patients from 23 studies in severity analysis. No increased risk of mortality [Pooled OR 0.91 (0.65-1.26), I 2  = 89%] or severity [Pooled OR 1.08 (0.79-1.46), I 2  = 88%] was seen with RAAS blockers. The drug class was protective in hypertension [pooled OR 0.63 (0.46-0.86), I 2  = 58%]. Severity of COVID-19 outcomes was high for Europeans [Pooled OR 2.08 (1.52-2.85), I 2  = 77%] and US patients [Pooled OR 1.87 (1.62-2.17)]. Nearly 4 times higher risk of hospitalization and 2 times higher risk of ICU admission and MV were observed in US patients. Class-wise, angiotensin receptor blocker use was associated with 1.6 times higher odds of severity, mainly in Europeans. Conclusion: RAAS blockers are not associated with increased mortality in COVID-19 patients and should be continued in hypertensives. US and European patients are at higher risk of severe outcomes. Pharmacogenetic differences may explain the ethnicity-related variations. Plain language summary Effect of RAAS-blocking medicines on COVID-19 Background and aims: Higher deaths have been observed in COVID-19 patients who have other long-term diseases such as heart disease, diabetes, and high blood pressure. Many of these patients are prescribed a class of medicines called RAAS blockers (ramipril, telmisartan, etc). We studied whether the use of these medicines worsens the course of COVID-19 disease in these patients or causes excess deaths. Methods: We conducted a pooled analysis of 47 observational studies on the use of RAAS blocker drugs in COVID-19 patients. Results: We found that RAAS blockers do not cause excess deaths in patients with COVID-19. On the contrary, they have benefits if prescribed to those with high blood pressure. We also found that whereas European and US patients of COVID-19 taking these medicines had higher disease severity, this was not the case for Chinese patients. Conclusion: Theremay be some genetic and other factors responsible for differences by ethnicity.